Why satisfy preferences? - Daniel M. Hausman (Max Planck Institute of Economics, 2011)
Contemporary mainstream normative economists assess policies in terms of their capacities to satisfy preferences, though most would concede that other factors such as freedom, rights, and justice are also relevant. Why should policy be responsive to preferences? This essay argues that the best reason is that people's preferences are in some circumstances good evidence of what will benefit them. When those circumstances do not obtain and preferences are not good evidence of welfare, there is little reason to satisfy preferences.
Keywords: 330; Präferenztheorie; Wirtschaftspolitik; Wohlfahrtseffekt; Kritik; Theorie